PKC Inhibits Sec61 Translocon-Mediated Sarcoplasmic Reticulum Ca2+ Leak in Smooth Muscle Cells - Dagnino-Acosta, Adan; Guerrero-Hernandez, Agustín (Frontiers in Physiology, 2022)
PPKC inhibitors stimulate Ca2+ release from internal stores in diverse cell types. Our data indicate that this action cannot be explained by an increased agonist-induced IP3 production or an overloaded SR Ca2+ pool in smooth muscle cells from guinea pig urinary bladder. The incubation of these cells with three different PKC inhibitors, such as Go6976, Go6983, and BIM 1, resulted in a higher SR Ca2+ leak revealed by inhibition of the SERCA pump with thapsigargin. This SR Ca2+ leakage was sensitive to protein translocation inhibitors such as emetine and anisomycin. Since this increased SR Ca2+ leak did not result in a depleted SR Ca2+ store, we have inferred there was a compensatory increase in SERCA pump activity, resulting in a higher steady-state. This new steady-state increased the frequency of spontaneous outward currents (STOCs), which reflect the activation of high conductance, Ca2+-sensitive potassium channels in response to RyR-mediated Ca2+ sparks. This increased STOC frequency triggered by PKC inhibition was restored to normal by inhibiting translocon-mediated Ca2+ leak with emetine. These results suggest a critical role of PKC-mediated translocon phosphorylation in regulating SR Ca2+ steady-state, which, in turn, alters SR Ca2+ releasing activity.